Effect of selected Indonesian plants on Giardia intestinalis in an experimental in vitro model - Pecková, Radka; Doležal, Karel; Sak, Bohumil; Květoňová, Dana; Kváč, Martin; Petřík, Ivan; Nurcahyo, Wisnu; Foitová, Ivona (BMC complementary medicine and therapies, 2025)
BACKGROUND: This study evaluated in vitro antigiardial activity in four Indonesian plants (Archidendron fagifolium, Diospyros sumatrana, Piper betle and Shorea sumatrana) extracted in methanol, methanol-tetrahydrofuran, and water. These plants exhibiting promising anti-parasitic activity were selected on the basis of collected behavioral data and their ability to decrease parasite load in Sumatran orangutans. Extracts of Arabidopsis thaliana, a plant routinely used as a laboratory model in research, were used as a negative control. METHODS: Plant extracts of different concentrations (400, 100, 25 and 6.25 µg/ml) and metronidazole (100 µg/ml), a standard giardicidal drug, were incubated with 25,000 trophozoites per milliliter of growth medium in 12-well tissue culture plates under anaerobic conditions for 72 h. Cultures were counted in a hemocytometer using a light microscope and then statistically evaluated. The cytotoxicity of the extracts was determined by the MTT Cell Viability Assay. RESULTS: We recorded a statistically-significant decrease in giardia trophozoites in two extracts: the methanolic extract of A. fagifolium (Kruskal-Wallis: p = 0.013) and the aqueous extract of P. betle (Kruskal-Wallis: p = 0.002). Effective concentrations of 400 µg/ml and 100 µg/ml, respectively, were revealed. Cytotoxicity was not demonstrated. CONCLUSIONS: The results of our study show that extracts of A. fagifolium and P. betle have potential as an alternative treatment of G. intestinalis infection. This is the first scientific proof of the biological activity of A. fagifolium, confirming the assumption that orangutans use this plant (as well as P. betle) for self-medication.
Keywords: Piper betle; Giardia intestinalis; Antiprotozoal Agents; Indonésie; antiprotozoální látky; Antigiardial activity; Plant Extracts; Natural antiparasitic; Animals; Giardia lamblia; Diospyros; Drug of choice; zvířata; Parasite; Indonesia; rostlinné extrakty